A Study on Use of Modern Technology in Education for Learning and Teaching: Exploring the Impact of Modern Technology on Learning and Teaching (Journal of Advances and Scholarly Researches in Allied Education, 2020)
God gave us technology as a gift. It is possibly the greatest of God's gifts, following the gift of life. It spawned entire civilizations, as well as the arts and sciences. As a result of advancements in technology, our way of life has undergone significant transformation. In many ways, it has transformed the way we think about what it means to live. There is no denying that technology has a significant impact on nearly every aspect of our lives. Thanks to technology improvements, many previously manual processes can now be automated. In addition, contemporary technology has made it possible to execute numerous difficult and vital processes with increased ease and efficiency. In recent years, technology has become increasingly integrated into our daily lives, making it easier for us to acquire vast amounts of information. Pupils nowadays have grown up in a technologically advanced world. When new technologies, such as audio and video cassettes, CDROMs, DVDs, personal computers (PCs), or iPods, become accessible, attempts are usually made to adapt them for educational purposes. Many Web 2.0 tools, such as wikis, blogs, and podcasts, have been repurposed for instructional purposes by professional educators.